Atitudes frente a mídia de tela: efeitos do uso problemático em comportamento pró-social de crianças - Carvalho, Thayro Andrade (2024)
The objective was to verify the effect of screen media on the development of pro-social behavior in children. To this end, we conducted five studies. The first study carried out a bibliographic survey to verify evidence of the relationship between screen media and pro-social behavior in children. The findings indicated the potential of screen media as a variable capable of stimulating prosocial behavior, in addition to parental control over screen use. Concomitantly, three psychometric studies were carried out, (2) to develop the Attitudes towards Screen Media Scale for Children - EAMT-C, (3) the Attitudes towards Screen Media Scale for Parents - EAMT-P, and (4) to validate the Problematic Use of Screen Media measure, and a final correlational study (5) verified the mediation effect of problematic use of screen media on attitudes and pro-social behavior. Study 2 consisted of two stages, exploratory and confirmatory, both with an average of 200 children, primarily from the state of Piauí, answering the EAMT-C and a sociodemographic questionnaire. The results indicated an adjusted psychometric structure, both exploratory and confirmatory, with four items and the potential to measure attitudes towards screen media in children. Study 3 presented psychometric evidence for a single-factor measure capable of assessing attitudes towards screen media in parents (ꞷ = 0.87). In Study 4, the PMUM was translated and tested. The PMUM was administered to 400 mothers and fathers of children (aged between 5 and 12) from all over Brazil, divided equally into two studies, exploratory and confirmatory. The results indicated that the measure had a single-factor structure similar to the original measure, with nine items and satisfactory indices (ꞷ = 0.90). The fifth study used correlational analysis to verify the relationship between the variables, confirming that problematic use of screen media has a negative effect on the relationship between parental attitudes and children's pro-social behavior. Finally, the impact that screen media can have on children's daily lives was highlighted, establishing media as a highly relevant variable in the development of children's behaviors.